Primary mediastinal large B-cell lymphoma and pregnancy: a challenging clinical scenario - Intravaia, Rita; De Chiara, Benedetta; Musca, Francesco; Casadei, Francesca; Santambrogio, Gloria; Spanò, Francesca; Belli, Oriana; Quattrocchi, Giuseppina; Giannattasio, Cristina; Moreo, Antonella (Monaldi Archives for Chest Disease, 2022)
A 26-weeks pregnant woman presented with progressively worsening dyspnoea and poor general conditions. Using low-dose radiation multi-imaging techniques and thoracic biopsy a primary mediastinal large B cell was diagnosed. A multidisciplinary approach identified the correct hemodynamic management, the best therapeutic strategy and the timing for delivery.